An Algorithm for Mapping Relational Database to Resource Description Framework - K.Elbashir, Murtada; A.Aboelhassan, Mohamed; A.Ali, Abu baker (Gezira Journal of Engineering and Applied Sciences, 2018)
The Resource Description Framework (RDF) is one of the World Wide Web Consortium (W3C) specifications and it is part of W3C semantic web activities. Its main idea is to make the statements about web resources in the form of subject–predicate–object expressions. Relational databases are considered to be the main sources for the web. To integrate them into semantic web, they should be mapped to RDF. The aim of this study is to design a tool that converts relational databases to RDF based on direct mapping method. The designed tool can express the Meta data of relational database in a minimally constrained, flexible, but meaningful way so that web data can be exchanged and integrated without loss of semantics.